Bezpieczeństwo ruchu drogowego jako przedmiot badań naukowych .......... 151 - Ostrowska, Martyna (Systemy bezpieczeństwa: Wymiar lokalny i państwowy, 2020)
Data from the World Health Organization report shows that every year 1.3 million people die on the roads of the world, and 20 to 50 million are seriously injured. Road transport is the most dangerous means of transport. A fatal accident in the world happens every 50 seconds. For this reason, the issue of road safety is taken up in social research and is a significant research problem. The article presents the specifics of road safety as an object of scientific research, in particular theoretical and methodological aspects.